Drenagem urbana em áreas especiais: o caso da bacia fechada do bairro de Oitizeiro, João Pessoa. - Santos, Valéria Diniz dos (2006)
Nowadays, problems including urban drainage are increasing with the percentage of urban area. In fact, the quality of life in big cities is directly affected by the drainage problems. In case of special areas, such as a closed watershed, the problems are increasing because in this sort of watershed there is not an outlet. This peculiar characteristic in its relief or its soil uses originates diversified questions about hidrology, sedimentology and water quality. In this paper, it was made a study about urban drainage problems in a watershed called Lagoa do Buracão, in the city of João Pessoa, State of Paraíba, Brazil. Each feature of the studied area was researched and several hydrological simulations were made in order to analyze three different sceneries of the soil occupation. The sceneries include changes in the level of the lake. It was used rainfall data and physical characteristics of the studied watershed. The results showed that the satisfactory scenery is the first one. Important positive impacts are involved with the proposed solution as well as negative impacts too. The main conclusion is that the proposal solution is highly recommendable for the resolution of the problem of urban drainage of Lagoa do Buracão. It adds other functions as the creation of a desirable landscape in the composition of the urban space, the valuation of the neighboring areas and the restoration of the environment which is currently degraded.